The Effectiveness of Zooming In and Zooming Out Strategy on Student’s Reading Comprehension in Descriptive Text at the First Grade of Islamic Senior High School AL Wahid Kepung - Novi Rina Dewi; Mualimin (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2021)
This study was conducted to know the effectiveness of using ZIZO strategy on students’s reading comprehension in descriptive text according to Karen D. Wood and Janis M. Harmon (2001; 53). This research used quantitative approach with pre-experimental research design. The population of this research was the first grade of Islamic Senior High School Al Wahid Kepung. The sample of this research was X IPA class consisting 20 students. The research instrument was pre-test and post-test with the format of multiple choices consisting 20 items pre-test and post-test. The data analyze by t-test using SPSS version 30. The result of the analysis showed that mean of pre-test was 72.00. And the result of the mean of post-test was 83.25. So, the result of the research was stating that applying using ZIZO strategy in teaching reading comprehension was effective. It was proved by the significant different score of student’s reading comprehension before and after taught by using ZIZO strategy. The significance value was 0.000 and the significance level was 0.05. it means that the significance value was smaller than significance level (0.000 < 0.05). So, the alternative hypothesis (H1) was accepted and null hypothesis (H0) was rejected. It means that the using of ZIZO strategy gives positive effect to the students’ reading comprehension.